Towards a Domain Specific Modeling Language for Agent-Based modeling of Land Use/Cover Change - Grueau, Cédric (2013)
While agent-based models are widely used for the simulation of human-natural systems, it remains challenging for scientists to specify their models in a manner in which they can be understood and used by others. In this research project, we survey existing solutions that have emerged to cope with models specification issues. We then propose another approach: a domain specific modeling language for agent-based simulations of land use/cover change. This language is intended to constitute a means to promote models’ validation and reuse. We also present the general methodology for the development of the modeling language which consists in extending existing conceptual modeling languages with domain-specific language profiles. We also present the first step towards its development comprising a domain model based on a domain ontology.